2000
DOI: 10.3348/kjr.2000.1.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Recurrent Uterine Cervical Cancer: Computed Tomography versus Positron Emission Tomography

Abstract: ObjectiveTo determine the accuracy of CT and positron emission tomography (PET) in the diagnosis of recurrent uterine cervical cancer.Materials and MethodsImaging findings of CT and PET in 36 patients (mean age, 53 years) in whom recurrent uterine cervical cancer was suspected were analyzed retrospectively. Between October 1997 and May 1998, they had undergone surgery and/or radiation therapy. Tumor recurrence was confirmed by pathologic examination or follow-up studies.ResultsIn detecting recurrent uterine ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 23 publications
0
33
0
3
Order By: Relevance
“…In Park's study [13] , they found PET was much better than CT by reporting that the sensitivity and specifi city of CT scans was 77% and 83% respectively, and the sensitivity and specificity of PET scans was 100% and 94% respectively. Rose et al [9] indicated that PET was better than CT for lymph node detection.…”
Section: Discussionmentioning
confidence: 94%
“…In Park's study [13] , they found PET was much better than CT by reporting that the sensitivity and specifi city of CT scans was 77% and 83% respectively, and the sensitivity and specificity of PET scans was 100% and 94% respectively. Rose et al [9] indicated that PET was better than CT for lymph node detection.…”
Section: Discussionmentioning
confidence: 94%
“…Several authors have investigated the usefulness of PET for postoperative or post-therapy surveillance of patients with cervical cancer and found that the sensitivity, specificity, and accuracy were 86-100%, 60-94%, and 70-97%, respectively (Table 4) [12][13][14][15][16][17][18][19]. These studies revealed that false-negative cases included local recurrence in the retrovesical region, pelvic recurrence, lung metastasis, peritoneal dissemination, pelvic LN metastasis, and para-aortic LN metastasis, whereas false-positive cases were due to inflammatory lesions, physiological uptake, and postoperative change.…”
Section: Discussionmentioning
confidence: 97%
“…There have been several studies of FDG-PET [12][13][14][15][16][17][18][19] and only two reports of integrated FDG-PET/CT [20,21] describing their usefulness for the diagnosis of recurrent uterine cervical cancers. Chung et al [20] and Sironi et al [21] discussed the diagnostic accuracy of PET/CT, but did not compare PET/CT interpretation with PET-alone interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…PET scan is superior in the detection of lymph node metastasis compared to conventional imaging [27][28][29]. Patz et al evaluated a variety of focal pulmonary abnormalities by using a FDG PET, and determined a threshold of standardized uptake ratio (SUR) of 2.5 for optimal sensitivity and specificity of benign lesions.…”
Section: Discussionmentioning
confidence: 99%